An Evaluation of 20 Years of EU Framework Programme-Funded Immune-Mediated Inflammatory Translational Research in Non-Human Primates - Haanstra, Krista G.; Jonker, Margreet; ‘t Hart, Bert A. (Frontiers in Immunology, 2016)
Ageing western societies are facing an increasing prevalence of chronic inflammatory and degenerative diseases for which often no effective treatments exist, resulting in increasing health care expenditure. Despite high investments in drug development, the number of promising new drug candidates decreases. We propose that preclinical research in non-human primate can help to bridge the gap between drug discovery and drug prescription. Translational research covers various stages of drug development of which pre-clinical efficacy tests in valid animal models is usually the last stage. Pre-clinical research in non-human primates may be essential in the evaluation of new drugs or therapies when a relevant rodent model is not available. Non-human primate models for life-threatening or severely debilitating diseases in humans are available at the Biomedical Primate Research Centre (BPRC). These have been instrumental in translational research for several decades. In order to stimulate European health research and innovation from bench to bedside, the European Commission (EC) has invested heavily in access to non-human primate research for more than 20 years. BPRC has hosted European users in a series of transnational access programs covering a wide range of research areas with the common theme being immune-mediated inflammatory disorders. We present an overview of the results and give an account of the studies performed as part of European Union Framework Programme (EU FP)-funded translational non-human primate research performed at the BPRC. The data illustrate value of translational non-human primate research for the development of new therapies and emphasize the importance of EU FP funding